Unlocking Kautsky’s dark box: Development of an optical toxicity classification tool (OPTOX index) with marine diatoms exposed to emerging contaminants - Duarte, Bernardo (2022)
Chlorophyll a induction curves, or Kautsky curves, have been extensively used to study physiological stress conditions in phototrophic organisms, with the analysis of several derived parameters. Nevertheless, these variables use only about 10 % of the information comprised in the complete Kautsky curve dataset, leaving 90 % of the photochemical data within an underutilized dark box, that is not translated into photochemically relevant variables. By observing the variable fluorescence profiles from marine diatoms exposed to a myriad of emerging and classical contaminants, several fluorescence profile alterations were detected, with significant deviations from the control conditions concomitant with the degree of growth inhibition imposed by the chemical stressor. The Linear Discriminant Analysis (LDA) analysis based on the normalized variable chlorophyll a fluorescence profiles revealed a high discriminatory efficiency of the type of contaminant to which the cultures were exposed, indicating that the exposure to different chemical stressors (contaminants) results in specific fluorescence profiles that can be used as descriptors of these exposure conditions. Analysing the individual contaminant LDA analysis, a very low overlap between samples exposed to different concentrations was observed, indicating a high discriminatory power of the variable fluorescence profiles. When evaluating the blind-test classification efficiencies, provided by this contaminant-specific LDA approach, it was possible to observe a high degree of efficiency in almost all contaminants tested, and for most of the concentrations applied. With this in mind, the produced linear discriminants and proportion of traces was used to compute an optical toxicity classification tool - the OPTOX index. The index revealed a high degree of correlation with the growth inhibition observed and/or with the exogenous dose of contaminant applied. The developed OPTOX index, a unifying tool enclosing all the fluorescence data provided by the chlorophyll a induction curve, proved to be an efficient tool to apply in ecotoxicological assays using marine model diatoms with a high degree of reliability for classifying the exposure of the cells to emerging contaminants. Additionally, the data analysis pipeline, as well as the index development methodology here proposed, can be easily transposed to other autotrophic organisms subjected to different ecotoxicological test conditions calibrated and validated against known biochemical or morphological descriptors of stress, integrating this way a large amount of data that was until know completely overlooked and left within an underutilized and undervalued dark box.